Պատմական Սիւնիքի Բաղ գաւառի Երիցվանք-Արծուանիկ վանական համալիրը եւ բնակավայրը. տեղանուան ստուգաբանութիւն - Քումունց, Մհեր (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Ерицаванк расположен в провинции Багк исторического Сюника, Капанского района современного Сюникского марза. По преданию, название поселка Арцваник произошло от Ерицванка, в административную территорию которого входит церковный комплекс Ерицванк. В историко-археологических работах отмечается, что в Арцванике сохра- нились следы и памятники армянского поселения II—I тысячелетий до н. э. Сохранились также руины урартской крепости, захоронений и т. д. Ерицаванк упоминается в письменных источниках Мовсесом Каганкатваци, Степаносом Орбеляном, Гукасом Себастаци и другими. Единственная литографическая запись с упоминанием Ерицаванка сохранилась в Ваанаванке (1102 г.). Согласно преданиям, Еретсаванк (Երեցավանքն) получил свое название от армянского священнослужителя по имени Ерицак (Երիցակ). Возможно, после христианства топоним в разговорном языке подвергся некоторым изменениям. Происхождение топонима связано с образцом арцуи-еван-ик (արծուի- եւան- իք), который по той же народной этимологии мог стать Ерец (Երեծ), а затем Ерец ванк (Երեծ վանք) монастырь. Yeritsavank is located in the Bagh province of historical Syunik, Kapan region of today’s Syunik province. According to legend, the name of the village Artsuanik comes from Yeritsavank, the administrative territory of which includes the Yeritsavank monastic complex. Historical and archaeological works note that in Artsuanik there are traces and monuments of the Armenian settlement of the II-I millennia B.C. Ruins of a Urartian fortress, burial grounds, etc. are also preserved. Yeritsavank is mentioned in written sources by Movses of Kalankatu, Stepanos Orbelian, Ghukas of Sebastia and others. The only lithographic record mentioning Yeritsavank was preserved in Vahanavank (1102). According to the tradition, Yeretsavank (Երեցավանքն) got its name from an Armenian clergyman named Yeritsak (Երիցակ). Perhaps, after the adoption of Christianity the toponym was subjected to folk etymology. The origin of the toponym is related to the pattern Artsui-evan-ik (արծուի- եւան-իք), which by the same folk etymology could become Yerets (Երեծ), and then Yerets vank (Երեծ վանք) monastery.
Keywords: Պատմութիւն; Հայ եկեղեցւոյ պատմութիւն